2015
DOI: 10.1155/2016/9802136
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia‐Induced Carotid Body Chemosensory Potentiation and Hypertension Are Critically Dependent on Peroxynitrite Formation

Abstract: Oxidative stress is involved in the development of carotid body (CB) chemosensory potentiation and systemic hypertension induced by chronic intermittent hypoxia (CIH), the main feature of obstructive sleep apnea. We tested whether peroxynitrite (ONOO−), a highly reactive nitrogen species, is involved in the enhanced CB oxygen chemosensitivity and the hypertension during CIH. Accordingly, we studied effects of Ebselen, an ONOO− scavenger, on 3-nitrotyrosine immunoreactivity (3-NT-ir) in the CB, the CB chemosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Indeed, the time course of the BP elevation is consistent with the time required by CIH to significantly enhance CB chemosensory output. 19,24,29 Compatible with this interpretation, we previously found that external carotid arteries segments harvested from rats exposed to CIH for 21 days, present moderate increases in the contractile responses to KCl and reduced NO-dependent relaxation induced by acetylcholine. 45 Thus, it is plausible that more pronounced vascular changes may take place if CIH is prolonged for >28 days.…”
Section: Del Rio Et Al Carotid Body and Intermittent Hypoxia-related mentioning
confidence: 80%
See 2 more Smart Citations
“…Indeed, the time course of the BP elevation is consistent with the time required by CIH to significantly enhance CB chemosensory output. 19,24,29 Compatible with this interpretation, we previously found that external carotid arteries segments harvested from rats exposed to CIH for 21 days, present moderate increases in the contractile responses to KCl and reduced NO-dependent relaxation induced by acetylcholine. 45 Thus, it is plausible that more pronounced vascular changes may take place if CIH is prolonged for >28 days.…”
Section: Del Rio Et Al Carotid Body and Intermittent Hypoxia-related mentioning
confidence: 80%
“…7,19,24,29 At day 21 of CIH, bilateral CB ablation was performed and rats were kept in CIH for 7 more days ( Figure S1 in the online-only Data Supplement).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, our measurements of nitrotyrosine immunoreactivity reflect production of peroxynitrite, the rapidly-formed product of the interaction between superoxide and nitric oxide. Recently, evidence has emerged that CIH-induced sensitization of chemoreflex pathways is critically dependent on peroxynitrite (Moya et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…We measured nitrotyrosine, a marker of the free radical oxidant, peroxynitrite, as an indicator of oxidative stress in carotid bodies (Del Rio et al, 2010, 2011a; Moya et al, 2016). At the end of 21 d of CIH or NORM exposures, the rats were deeply anesthetized with isoflurane and transcardially perfused with PBS to clear the red cells, followed by perfusion with 4% paraformaldehyde in PBS (300–500 ml, 25 ml/min).…”
Section: Methodsmentioning
confidence: 99%